Digital E-Booklet as an Innovative Promotional Media for Gravity Adventure Rafting Tourism in Pangalengan Regency - Gugun Gunawan (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: This study aims to evaluate the effectiveness of using a Flip HTML5-based rafting e-booklet in enhancing the quality of the user interface when accessing information about rafting activities in Pangalengan, as well as to examine its influence on the potential increase in tourist visits. Method: This study employs a quantitative approach, with data collected through questionnaires distributed to rafting visitors, field observations, and documentation review. Result: The findings of this study indicate that the developed e-booklet is effective and feasible to be used as a promotional medium. The information presented in the e-booklet is considered comprehensive and clear, aligning with the needs of tourists seeking rafting activities in Pangalengan. Furthermore, the interactive features provided by Flip HTML5 enhance the user interface experience, thereby facilitating users in accessing and understanding the services offered. Contribution: This study contributes by recommending that PT. Djava Vista utilize the e-booklet not only as a medium for delivering essential information about rafting activities but also as a tool for implementing cross-selling strategies. By incorporating additional offerings such as other tour packages, documentation services, or accommodation facilities into the e-booklet, the company is expected to increase transaction value and expand business opportunities through more integrated and engaging promotional efforts.